2015
DOI: 10.1371/journal.pone.0116278
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 71 Virion-Associated Galectin-1 Facilitates Viral Replication and Stability

Abstract: Enterovirus 71 (EV71) infection causes a myriad of diseases from mild hand-foot-and-mouth disease or herpangina to fatal brain stem encephalitis complicated with pulmonary edema. Several severe EV71 endemics have occurred in Asia-Pacific region, including Taiwan, and have become a serious threat to children’s health. EV71 infection is initiated by the attachment of the virion to the target cell surface. Although this process relies primarily upon interaction between viruses and cell surface receptors, soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
(45 reference statements)
0
18
0
Order By: Relevance
“…The surface expression of hWARS in mock-and IFN-γ-treated NT2 and RD cells was further examined hWARS was further demonstrated in the orthogonal view of the anti-hWARS-stained RD cells treated with 0.1% Triton X-100 (Supplemental Video 1). Although many cellular factors have been shown to modulate the efficiency of EV-A71 entry (18,19), EV-A71 pathogenesis is generally attributed to the tissue expression patterns of 2 known cellular receptors: hSCARB2 and hPS-GL1 (6,7). Consistent with previous findings on the capacity of EV-A71 to bind to cellular receptors (20), our virus attachment assays by flow cytometry in nonpermeabilized transfected L929 cells also showed an increased capacity of EV-A71 to bind to the surface of hSCARB2-and hPSGL1-transfected L929 cells when compared with mock-transfected L929 cells ( Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…The surface expression of hWARS in mock-and IFN-γ-treated NT2 and RD cells was further examined hWARS was further demonstrated in the orthogonal view of the anti-hWARS-stained RD cells treated with 0.1% Triton X-100 (Supplemental Video 1). Although many cellular factors have been shown to modulate the efficiency of EV-A71 entry (18,19), EV-A71 pathogenesis is generally attributed to the tissue expression patterns of 2 known cellular receptors: hSCARB2 and hPS-GL1 (6,7). Consistent with previous findings on the capacity of EV-A71 to bind to cellular receptors (20), our virus attachment assays by flow cytometry in nonpermeabilized transfected L929 cells also showed an increased capacity of EV-A71 to bind to the surface of hSCARB2-and hPSGL1-transfected L929 cells when compared with mock-transfected L929 cells ( Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Given the fact that humidex as an index tends to be greater than temperature (as shown above, the maximum temperature was around 30 °C, whereas the peak humidex was above 40), the second threshold detected in the present research should be similar to that identified in the previous study. This threshold might result from interactions among biological mechanisms and human contact behaviors 9 28 . For instance, after the first minor peak, the promoting effects of humidex on the proliferation and transmission of HFMD-related enteroviruses might be predominant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that Gal1 promotes binding of viral envelope gp120 to CD4 + T cells, facilitating HIV-1 infection in a β-galactoside-dependent manner (30). Also, Gal1 promotes enterovirus 71 replication and enhances its infectivity (34). In contrast, Gal1 binding to N-linked oligosaccharides of hemagglutinin and neuraminidase from influenza virus masks relevant glycan structures and inhibits viral infection (31).…”
Section: Discussionmentioning
confidence: 99%
“…This includes the N-acetylglucosaminyltransferase 5 (MGAT5), an enzyme that generates β1-6-N-acetylglucosamine (β1-6GlcNAc)-branched complex N-glycans, which are the preferred intermediates for LacNAc extension (19). This prototype lectin has been implicated in glycan-mediated recognition, invasion, and evasion by various pathogens including parasites like Trypanosoma cruzi and Trichomonas vaginalis (25)(26)(27)(28) and viruses such as the human T-cell leukemia virus-1, HIV-1, influenza virus, dengue virus, Epstein-Barr virus, Nipah virus, and Enterovirus 71 (29)(30)(31)(32)(33)(34)(35).…”
mentioning
confidence: 99%